Enhancing Creative Thinking Abilities and Mathematical Thinking Dispositions in Elementary Students - Samsudin, Samsudin; Wahyudin, Wahyudin; Arisetyawan, Andika (Papanda Publisher, 2025)
Creative thinking abilities and mathematical thinking dispositions represent critical competencies in elementary mathematics education, yet limited research examines their simultaneous development through targeted pedagogical interventions. This study investigated differences in creative thinking abilities and mathematical thinking dispositions between elementary students receiving differentiated instructional treatments. A quasi-experimental design with non-equivalent control groups was employed, involving 60 fifth-grade students from SD Negeri Sentul 1, divided into experimental (n=30) and control (n=30) groups. Creative thinking ability was measured using an essay test based on Guilford's four-dimensional framework (fluency, flexibility, originality, elaboration), while mathematical thinking disposition was assessed through a four-point Likert scale questionnaire encompassing curiosity, perseverance, open-mindedness, self-confidence, and reflectivity. Data were analyzed using independent samples t-tests following normality and homogeneity assumption testing. Significant differences emerged between groups across all measured constructs (p<0.05). The experimental group demonstrated superior creative thinking ability (M=82.6 vs. M=73.9, Cohen's d=1.18) and more positive mathematical thinking disposition (M=3.42 vs. M=2.94, Cohen's d=1.06). Elaboration showed the largest creative thinking difference (9.6 points), while open-mindedness exhibited the greatest dispositional improvement (0.53 points). Findings provide empirical evidence that targeted instructional approaches can simultaneously enhance cognitive abilities and affective dispositions in mathematics learning. The synergistic relationship between creative thinking and positive dispositions challenges traditional pedagogical models that address these dimensions separately. Results support implementing learning environments that encourage exploration, multiple solution strategies, and reflective practices to develop both mathematical competencies and positive attitudes toward mathematics in elementary education.